Assessing the influence of environmental niche segregation in ammonia oxidizers on N2O fluxes from soil and sediments. (February 2022) - Lin, Yu-Pin; Ansari, Andrianto; Wunderlich, Rainer Ferdinand; Lur, Huu-Sheng; Ngoc-Dan Cao, Thanh; Mukhtar, Hussnain
Abstract: Understanding the environmental niche segregation of ammonia-oxidizing archaea (AOA) and bacteria (AOB) and its impact on their relative contributions to nitrification and nitrous oxide (N2 O) production is essential for predicting N2 O dynamics within an ecosystem. Here, we used ammonia oxidizer-specific inhibitors to measure the differential contributions of AOA and AOB to potential ammonia oxidization (PAO) and N2 O fluxes over pH (4.0–9.0) and temperature (10–45 °C) gradients in five soils and three wetland sediments. AOA and AOB activities were differentiated using PTIO (2-phenyl-4, 4, 5, 5-tetramethylimidazoline-1-oxyl 3-oxide), 1-octyne, and acetylene. We used square root growth (SQRT) and macromolecular rate theory (MMRT) models to estimate cardinal temperatures and thermodynamic characteristics for AOA- and AOB-dominated PAO and N2 O fluxes. We found that AOA and AOB occupied different niches for PAO, and soil temperature was the major determinant of niche specialization. SQRT and MMRT models predicted a higher optimum temperature for AOA-dominated PAO and N2 O fluxes compared with those of AOB. Additionally, PAO was dominated by AOA in acidic conditions, whereas both AOA- and AOB-dominated N2 O fluxes decreased with increasing pH. Consequently, net N2 O fluxes (AOA and AOB) under acidic conditions were approximately one to three-fold higher than those observed in alkaline conditions. Moreover, structural equation and linear regression modeling confirmed a significant positive correlation ( R 2  = 0.45, p  < 0.01) between PAO and N2 O fluxes. Collectively, these results show the influence of ammonia oxidizer responses to temperature and pH on nitrification-driven N2 O fluxes, highlighting the potential for mitigating N2 O emissions via pH manipulation. Graphical abstract: Image 1 Highlights: The relative contributions of AOA and AOB to PAO strongly varied across a temperature gradient. High N2 O emissions occurred under acidic (pH 5) rather than alkaline conditions (pH 9). N2 O emissions increased with nitrification, particularly for AOA-dominated slurries.